DETERMINING THE PHYSICO-MECHANICAL CHARACTERISTICS OF MAIZE STALKS FORDESIGNING HARVESTER - A.Y. Şeflek (Journal of Animal and Plant Sciences, 2017)
Physical characteristics of crops and plants are significant issues in designing machinery to harvest them.Therefore in the present study, general physical properties, bending stress, modulus of elasticity, shear stress and specific shearing energy were determined over stalks of 10 different maize (Zeamays L.) cultivars. Test specimens were taken from three different locations of stalks as of upper section, middle section and bottom section. Average moisture contents of upper, middle and bottom sections were respectively observed as 78.18, 73.87 and 69.91%. The average bending force varied between 40 -459.3N and the average modulus of elasticity varied between 10.04- 673.84 MPa. The modulus of elasticity decreased with increasing stalk diameters. Variance analysis revealed that Bora, SX-689, MocejonI and DK-585 were similar cultivars and their modulus of elasticity were greater than the other cultivars (P<0.01). The results also showed decreasing shearing stress and specific shearing energy values toward the upper sections of the stalks. The maximum shearing stress and the specific shearing energy were 5.27MPa and 213.03 mJmm-2, respectively. According to variance analysis, the cultivarsSX-689 and Mocejon-I were also found to be as similar varieties and their specific shearing energies were greater than the other cultivars (P < 0.01). Both the shearing stress and specific shearing energy were found to be higher along the bottom section of the stalks due to the structural heterogeneity.
Keywords: Maize; bending stress; modulus of elasticity; shearing stress; specific shearing energy